PENGARUH MASSAGE COUNTERPRESSURE TERHADAP PENURUNAN NYERI IBU BERSALIN KALA I: SYSTEMATIC LITERATUR REVIEW - Pebri Fitri Lestiawati; Diah Warastuti Diah; Lisa Trina Arlym (JURNAL KESEHATAN DAN KEBIDANAN, 2022)
Labor pain can cause anxiety in laboring mothers and interfere with comfort during childbirth. Pain management of labor contractions that can be done, among others, is themethod counterpressure massage. The purpose of this study was to determine the effect of Massage Counterpressure on the level of pain during the first stage of labor. The method used in this study was a Systematic Literature Review using database asearch Google Scholer, Research Gate, Science Direct and PubMed from 2016 to 2021 and theselection process literature using PRISMA diagrams. There are three Research Questions (RQ) set in this study. The final results obtained by the study were 6 articles, from these 6 articles there was a decrease in the lowest average pain score after giving massage counterpressure by 3.2. The conclusion is that giving counterpressure massage has a good effect on pain levels in maternity so that it can help facilitate the delivery process and reduce the incidence of prolonged labor and other complications during childbirth. The suggestion of this research is Massage Counterpressure can be recommended as a complementary therapy and applied to relieve pain during labor.Keywords : Massage Counterpresure, Pain Labor